Research on application of variable coding modulation system based on Digital Video Broadcasting ‐ Satellite ‐ 2nd Generation in data transmission of near‐earth remote sensing satellite. (5th May 2020) - Zhang, Shasha; Cao, Haiyi; Zhang, Xinwei; Yao, Xinyu; Zhao, Chenguang
Summary: In order to make full use of the link resources for data transmission from near‐earth remote sensing satellites, variable coding modulation (VCM) system is used to fully utilize the system link margin to improve the satellite data transmission performance. By analyzing the dynamic link under the VCM data transmission system, the contribution of the VCM system to the satellite data link optimization is studied from the perspective of engineering application, which can provide reference for the data link design of remote sensing satellites. Applying the flow design, for the currently adopted transmission system of X band, compared with traditional constant coding modulation (CCM) system, the average link performance of VCM system can be increased by 42.1% in single‐station transmission mode and 53.3% in dual‐station relay mode through the exampled analysis. Abstract : In order to make full use of the link resources for data transmission from near‐earth remote sensing satellites, variable coding modulation (VCM) system is used to improve the satellite data transmission performance. By analyzing the dynamic link under the VCM data transmission system, the contribution of the VCM system to the satellite data link optimization is studied from the perspective of engineering application, which can provide reference for the data link design of remote sensing satellites.